The Story "Bedouins of Jewish Origin" by Rachel Yanait Ben-Zvi: A Content Analysis with a Translation of the Story into Arabic - Amarat, Mahmoud (Dirasat: Human and Social Sciences, 2022)
After its occupation of Arab territory, the Zionist movement sought to destroy every Arab aspect. It has also attempted to erase, falsify and rewrite history in a manner consistent with its aspirations and goals in addition to obliterating the Palestinian and Arab identity. This movement has recruited Hebrew Literature to serve its Zionist purposes and to achieve its goals. This study came to highlight one of these Zionist theses, which claims that the origins of majority of Palestinian peasants and some tribes in eastern Jordan belong to a Jewish origin, and that they were forced to convert to Islam. The Israeli writer Rachel Yinnait Ben-Zvi has adopted this proposition in many of her writings, including her story "Bedouins of Jewish Origin". In its first part, the present study addresses the Zionist claims about the origin of the Palestinian farmers as well as the Bedul and Liathneh tribes. As for the second part, it is devoted to the study of Rachel Yannait’s biography, the content of her story, as well as its translation into Arabic. The researcher concluded his study with a presentation of the most important results of the study.